Research on Big Data Platform and Key Technologies for Inventory Management of Carriers - TeamofBigDataforInventoryManagement Project; TeamofUserAwareNetworkOperationandMaintenance Project (Dianxin kexue)
Carriers need to shift from incremental to inventory management.It was presented that big data platform and key technologies played the important roles in inventory management.The proposed technologies could solve the existing problems in current carrier's supporting systems,and better business results were achieved in Shanghai Unicom business practice.